Effectiveness of high-frequency repetitive transcranial magnetic stimulation in patients with depression and Parkinson’s disease: a meta-analysis of randomized, controlled clinical trials - Qin B (Dove Medical Press, 2018)
Bin Qin,1,* Hong Chen,1,* Wen Gao,1,* Li-Bo Zhao,2,* Ming-Jun Zhao,3 Hui-Xun Qin,1 Ming-Xiu Yang1 1Department of Neurology, Affiliated Liuzhou People’s Hospital of Guangxi University of Science and Technology/Liuzhou People’s Hospital, Liuzhou, 2Department of Neurology, Yongchuan Hospital of Chongqing Medical University, Chongqing, 3Department of Pharmacy, The Second Affiliated Hospital of Xinxiang Medical University (Henan Mental Hospital), Xinxiang, China *These authors contributed equally to this work Aim: This meta-analysis aimed to assess the effect of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) for the treatment of depression in patients with Parkinson’s disease (PD). Methods: The design was a meta-analysis of randomized controlled trials (RCTs). The participants were patients with PD who suffered from depression. The interventions were HF-rTMS alone or in combination with other treatments compared with sham-rTMS, placebo, and antidepressant treatments. The primary outcome measure was changes in depressive symptoms, defined as the mean change in the total depression score. The secondary outcome was changes in motor symptoms, defined by Unified Parkinson’s Disease Rating Scale part III scores, and the acceptability, defined as the risk of all-cause discontinuation. These were expressed as mean differences (MDs), standardized mean differences (SMDs), or risk ratios (RRs) with 95% confidence intervals (CIs). Results: We identified nine suitable trials, with data from 332 participants. For the patients with depression in PD, HF-rTMS was not better than sham-rTMS (SMD =-0.33, 95% CI -0.83 to 0.17) or selective serotonin re-uptake inhibitors (SSRIs) (SMD =0.07, 95% CI -0.52 to 0.18) for the treatment of depressive symptoms. However, the motor benefits after treatment with HF-rTMS might be better than sham-rTMS (MD =-2.80, 95% CI -5.45 to -0.15) and SSRIs (MD =-2.70, 95% CI -4.51 to -0.90). Conclusion: This meta-analysis provides some evidence that in patients with PD with depression, HF-rTMS may lead to improvement in motor function but not in depression compared with sham-rTMS or SSRIs. Keywords: sham-repetitive transcranial magnetic stimulation, selective serotonin re-uptake inhibitors, depressive symptoms, motor symptoms